Chi's sweet adventures. 4 - Konami, Kanata, 1958-; Cash, Jan; Natsume, Kinoko ([New York, NY] : Vertical, Inc., 2019)
It's summertime and the kittens look for a way to cool off. Chi and Cocchi are given a tasty treat, but find that every cat in town wants a piece of it. Then Yohei wonders what Chi does when she's not at home and decides to follow her...
Translated from the Japanese.
Keywords: Kittens -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Cat owners -- Comic books, strips, etc; Human-animal relationships -- Comic books, strips, etc; Comic books, strips, etc. -- Japan -- Translations into English -- Comic books, strips, etc; Cartoons and comics; Graphic novels; Comic books, strips, etc; Graphic novels; Comics (Graphic works)